Changes in the credit risk profile of polish local governments. An assessment of unsystematic risk - Kluza, Krzysztof (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper presents research devoted to changes in the local government credit risk profile in Poland. Firstly, the risk assessment is conducted based on the free operating cash flow and net debt approach as a preferred alternative to the statutory debt limits. Then, using the Data Envelopment Analysis method, an analysis is conducted of changes of unsystematic risk of local government subcategories during the period of economic slowdown. The study finds that the general risk profile of local governments strongly deteriorated compared to the pre-crisis year of 2008. Since 2011 it has slightly improved. However, this partial improvement was mainly due to a drop in market interest rates in 2013. Adjusting data for this factor reveals that the financial standing would not have changed in a positive way. Two local government subcategories have relatively inferior risk profiles. The first one is the towns with county rights, which represent more than one third of the population and revenues of the local government sector. They have the highest debt levels compared to their debt service capacities, and some of them accumulated high unsystematic risk. Approximately 20% of them have debt service indicators below safe levels. The second category is the counties. Despite relatively low debt levels, there is high systematic risk in this group. Without system reform of the counties, approximately 25% of them may have problems with performing their statutory tasks or servicing their debt in the medium term. The rural boroughs are the safest local government category in Poland
Argumenta Oeconomica, 2017, Nr 1 (38), s. 167-192
Keywords: local government debt; local government risk; unsystematic risk; DEA method